A clinical analysis of Candida tropicalis bloodstream infections associated with hematological diseases, and antifungal susceptibility: a retrospective survey - Beibei Yang; Zhenbin Wei; Meiqing Wu; Yongrong Lai; Weihua Zhao (Frontiers in Microbiology, 2023)
Summary objectiveTo assess the clinical features and outcomes of hematological disease patients with Candida tropicalis bloodstream infections and determine the antifungal susceptibility of C. tropicalis.MethodsThis is a retrospective, single-center, observational study conducted in the Department of Hematology at The First Affiliated Hospital of Guangxi Medical University from January 2013 to December 2021. A total of 26 hematological disease patients with C. tropicalis bloodstream infections were enrolled, and their clinical features, treatment plans, and prognoses were assessed. Univariate analysis was performed by Kaplan–Meier analysis and multivariate analysis was conducted using a Cox regression model. The antifungal susceptibility of C. tropicalis was determined from patient blood cultures.ResultsThe patients had a mean age of 35 years (range: 10–65 years), 50% were male (13/26) and 88.5% had hematologic malignancies (23/26) while the remaining three patients included two cases of severe aplastic anemia and one case of β-thalassemia. All patients had neutropenia. Seven patients were initially given azole alone (26.9%), five of whom failed treatment and died (71.4%). Fifteen patients were treated with echinocandin (57.7%), three of whom failed treatment and died (20.0%), and eight patients were treated with amphotericin B (30.8%), two of whom failed treatment and died (25.0%). The total and attributable mortality rates were 42.3 and 34.6%, respectively. Univariate analysis showed that there are six risk factors for attributable deaths among hematological disease patients with C. tropicalis blood infections. These risk factors included septic shock, Pitt bacteremia scores ≥4, procalcitonin levels ≥10 ng/mL, positive plasma (1,3)- β-D glucan assay, serum albumin levels <30.0 g/L, time from fever to antifungal treatment initiation ≥5 days and time between neutropenia and antifungal treatment ≥10 days. Moreover, skin and mucosal infections and a treatment schedule that included amphotericin B and drug combinations are protective factors for attributable deaths. Multivariate analysis showed that septic shock (p = 0.006) was an independent risk factor for attributable death. All isolates were sensitive to flucytosine and amphotericin B. The intermediate or resistance of C. tropicalis to fluconazole, itraconazole and voriconazole were 41.7, 50, and 41.7%, respectively.ConclusionHematological disease patients with C. tropicalis bloodstream infections had a high mortality rate, and early antifungal therapy significantly reduced mortality. Candida tropicalis was highly resistant to azole drugs and sensitive to flucytosine and amphotericin B. According to our study, the preferred agent is amphotericin B and drug combinations should be considered for severe infections.